A new species of succulent plants from the Muko-jima group of the Bonin Islands, Japan: Sedum mukojimense (Crassulaceae) - Ito, Takuro; Goto, Masafumi; Nakano, Hideto; Kokubugata, Goro (Phytotaxa, 2020)
A taxonomic re-examination of Sedum boninense, which is endemic to the Muko-jima and Chichi-jima groups of the Bonin Islands, Japan, was carried out. Morphological and physiological comparisons revealed differences between plants from the Muko-jima and Chichi-jima groups in the shape and size of leaves and underground bulb scale leaves, plant habit, habitat and flowering season. Molecular phylogenetic analysis using the ITS region revealed that the plants from respective island groups formed sister clades. Therefore, the plant from Muko-jima group is described as a new species of S. mukojimense.